Phospho-dependent interactions between NBS1 and MDC1 mediate chromatin retention of the MRN complex at sites of DNA damage. - Chapman, R; Jackson, S (2008)
Mammalian cells respond to DNA double-strand breaks (DSBs) by recruiting DNA repair and cell-cycle checkpoint proteins to such sites. Central to these DNA damage response (DDR) events is the DNA damage mediator protein MDC1. MDC1 interacts with several DDR proteins, including the MRE11-RAD50-NBS1 (MRN) complex. Here, we show that MDC1 is phosphorylated on a cluster of conserved repeat motifs by casein kinase 2 (CK2). Moreover, we establish that this phosphorylation of MDC1 promotes direct, phosphorylation-dependent interactions with NBS1 in a manner that requires the closely apposed FHA and twin BRCT domains in the amino terminus of NBS1. Finally, we show that these CK2-targeted motifs in MDC1 are required to mediate NBS1 association with chromatin-flanking sites of unrepaired DSBs. These findings provide a molecular explanation for the MDC1-MRN interaction and yield insights into how MDC1 coordinates the focal assembly and activation of several DDR factors in response to DNA damage.